Embracing linguistic diversity: Global Englishes language teaching for anti-racist education - Yunhua, Deng; Budiman, Asep (Frontiers in Education, 2024)
Racial inequalities persist in education, impacting various aspects, including language teaching. Traditional English language education has often favored standard English, inadvertently marginalizing non-native English speakers and users of diverse English varieties. This perpetuation of linguistic bias reinforces White hegemony within educational systems. This article contends that Global Englishes offers a promising approach to ameliorating racial inequalities in language education. It delves into the core principles of Global Englishes, scrutinizing linguistic, sociolinguistic, and sociocultural diversity and fluidity inherent in English use and its users in our globalized world. Furthermore, it explores how the Global Englishes Language Teaching (GELT) framework can promote equality, emphasizing best practices for implementing GELT to address racial inequalities. Global Englishes advocates for a more adaptable view of language, liberating nonnative speakers from native-speaker norms. Global Englishes places learner agency at the forefront, nurturing linguistic creativity, advocating for curricula that acknowledge multilingualism as the norm, and affirming learners' linguistic repertoires without reference to native norms. It also encourages a critical approach, analyzing the impact of prevailing standard language ideologies and White native-speakerism biases within learners' contexts. The article concludes by offering insights into future directions to address racial inequalities in education, emphasizing the importance of incorporating multiracial perspectives into educational frameworks.